Extensions of a TV Playout System to Support Dynamic Broadcast - Carstens, Jan Eike; Qi, Junge (Technische Universität Dortmund, 2013)
In this paper we present our approach to extend current TV playout systems to fulfil the requirements posed by the Dynamic Broadcast system. After a review of the Dynamic Broadcast system we analyze the new flexibilities in the content delivery and study the challenging use cases. The key requirement on the playout system deduced from the use cases is the support of a flexible delivery of individual packetized content fragments. In our solution we modify the workflow in the playout system, but reuse current playout devices and published standards for data transfer and schedule messaging. A delivery schedule optimized by the decision logic and represented in a BXF message structure is used to control the actions of the components in the playout system. Necessary changes to the signalling, packetizing and multiplexing modules are discussed and practical proposals for realization are presented. The concepts of our proposal have been implemented in a demonstrator.
Keywords: 620